Remarks on the Macrobiotus polyopus group, with the description of two new species (Eutardigrada, Macrobiotidae) - Pilato, Giovanni (Zootaxa, 2006)
Some problems are discussed concerning Macrobiotus polyopus Marcus, 1928 and its geographic distribution, and two new species are described: M. insularis sp. n. from Andaman Islands (attributed to M. polyopus by Maucci & Durante Pasa (1980)), and M. ocotensis sp. n. from southern Mexico. The validity of M. mandalaae Pilato, 1974 is confirmed. The hypothesis is advanced that also the Brazilian specimens recorded by de Barros (1942) do not belong to M. polyopus but to a different, probably undescribed, species.